Social psychology : a critical analysis from Islamic and scientific perspectives and application in industrial and organizational psychology - Mohd-Taib, M.; Alias, Alizi; Mohd-Taib, M.S. (2011)
The objective of this present theoretical paper is to provide an explanation on social psychology from Islamic perspective. The paper firstly discussed in general an overview of social affection, behaviour and cognition from Islamic point of view. Secondly, contemporary theories in social psychology were evaluated from both scientific and Islamic perspectives. Thirdly, the paper attempts to apply social psychology’s principles and theories to explain issues in applied field of Industrial/ Organizational Psychology. Finally, to embrace the importance of the role of human soul, an integrated model was proposed. The paper had referred to both psychology and Islamic psychology’s secondary sources. From Islamic perspective, whenever possible, explanation from Quran, Sunnah, Fiqh, Aqidah and Akhlaq perspectives were presented.